Clinical characteristics of 10 children with a pediatric inflammatory multisystem syndrome associated with COVID-19 in Iran - Leila Shahbaznejad; Mohammad Reza Navaeifar; Ali Abbaskhanian; Fatemeh Hosseinzadeh; Golnar Rahimzadeh; Mohammad Sadegh Rezai (BMC, 2020)
Abstract Background Although symptoms and signs of COVID-19 (Coronavirus disease 2019) in children are milder than adults, there are reports of more severe cases which were defined as pediatric inflammatory multisystem syndrome (PIMS). The purpose of this report was to describe the possible association between COVID-19 and PIMS in children. Methods From 28 March to 24 June 2020, 10 febrile children were admitted with COVID-19 infection showing characteristics of PIMS in Buali tertiary hospital of Sari, in Mazandaran province, northern Iran. Demographic and clinical characteristics, laboratory and imaging findings, and therapeutic modalities were recorded and analyzed. Results The mean age of the patients was 5.37 ± 3.9 years (13 months to 12 years). Six of them were boys. Kawasaki disease, myocarditis, toxic shock syndrome, appendicitis, sepsis, urosepsis, prolonged febrile seizure, acute hemorrhagic edema of infancy, and COVID-19-related pneumonia were their first presentation. All of them had increased C-reactive protein levels, and most of them had elevated erythrocyte sedimentation rate, lymphopenia, anemia, and hypoalbuminemia. Three of them had thrombocytopenia(PLT < 106). Six of them were serologically or polymerase chain reaction positive for COVID-19, and 4 of them were diagnosed as COVID-19 just by chest computed tomography scan. Most of the patients improved without a residual sequel, except one who died with multiorgan failure and another case was discharged with a giant coronary aneurysm. Conclusions Children with COVID-19 may present symptoms similar to Kawasaki disease and inflammatory syndromes. PIMS should be considered in children with fever, rash, seizure, cough, tachypnea, and gastrointestinal symptoms such as vomiting, diarrhea, and abdominal pain.